Pengaruh Penggunaan Aplikasi Belanja Online, Gaya Hidup, dan Literasi Keuangan terhadap Perilaku Konsumtif Maha-siswa PTN di Kota Surabaya - Aulia Wanda; Muslimin Muslimin (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the influence of the use of online shopping applications, lifestyle, and financial literacy on the consumptive behavior of students in four state universities in Surabaya. The problem raised is the high tendency to consummate students due to easy access to technology and different lifestyles and financial literacy skills. The purpose of the study was to analyze the contribution of these three variables in influencing consumptive behavior. The method used was a quantitative approach with data collection through a closed questionnaire distributed online, and data analysis using SmartPLS to test the relationship between variables. The results of the study showed that the use of online shopping and lifestyle applications had a significant effect on students' consumptive behavior, while financial literacy had a significant negative influence. These findings confirm that the ease of online shopping and consumptive lifestyles can increase consumptive behavior, but good financial literacy can suppress these tendencies. In conclusion, optimal financial literacy management is important to control consumptive behavior among students who actively use online shopping applications.